Design and Fabrication of Reverse Brake Applied in Hill Station - Lalchhanchhuaha; Thamotharan, C.; Naveenchandran, P. (International Journal of Psychosocial Rehabilitation, 2018)
In this work the mechanism has been developed to stop the vehicle from rolling backwards when the vehicle is moving in the hill roads. Ratchet and Pawl mechanism has been identified to arrest the motion to the front axle. Anti-Roll Back mechanism has been fabricated and tested on the front axle assembly. The mechanism works well.